Systems approach in construction – scientific school of a. A. Gusakov (social-communicative survey) - Zavadskas, Edmundas; Kaklauskas, Artūras (Journal of Civil Engineering and Management, 2003)
The scientific school of Academician A. A. Gusakov “Systems engineering in construction” has been approached by a social-communicative model. Scientists belonging to the above school have been identified and the period of the school formation has been determined. The research work carried out by A. A. Gusakov and his followers and their contribution to science and education have been discussed. The investigation is based on three methods: the analysis of the flow of theses, as well as the co-authorship and citation analysis.First Published Online: 26 Jul 2012